Implementasi Perbedaan Sistem Politik Berlandaskan Pancasila Dan Sistem Politik Islam Di Indonesia - Rahmadani, Muhammad Nur; Jalili, Ismail; Miinudin, Miinudin (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The Indonesian political system is officially based on Pancasila as the state ideology, while some community groups advocate an Islamic political system as an alternative. This study aims to: analyze the conceptual and implementation differences between the Pancasila and Islamic political systems in Indonesia; evaluate the impact of these differences on national and state life; and examine the relevance of both systems in the context of Indonesia's diverse society. The research method uses a qualitative approach through literature review of primary (the 1945 Constitution, MUI fatwas, sharia regulations) and secondary (30 journals published between 2010 and 2023) documents, as well as policy analysis of five cases of Islamic political implementation at the local level. The results reveal three main findings: First, the Pancasila political system is inclusive-pluralistic with a positivist legal source and a deliberative democratic structure, while the Islamic political system is based on sharia with the concept of hakimiyyah (God's sovereignty) and the caliphate model. Second, implementation in the field shows that Pancasila is more effective in maintaining social cohesion (a tolerance index of 72.3% according to SETARA 2022), while the application of Islamic politics tends to lead to polarization (conflicts increased by 40% in regions with sharia regulations). Third, despite fundamental differences, the synthesis of Islamic values within the Pancasila framework has proven to be able to create balance, as seen in the national education system that accommodates madrasahs. This study concludes that Pancasila remains the primary foundation of Indonesia's political system due to its ability to integrate diversity, but strengthening dialogue between Islamic and national values is needed to minimize ideological tensions.